Bypassing Primary Care Facilities for Childbirth: Findings from a Multilevel Analysis of Skilled Birth Attendance Determinants in Afghanistan. (9th February 2016) - Tappis, Hannah; Koblinsky, Marge; Doocy, Shannon; Warren, Nicole; Peters, David H.
Abstract : Introduction: The objective of this study was to assess the association between health facility characteristics and other individual/household factors with a woman's likelihood of skilled birth attendance in north‐central Afghanistan. Methods: Data from a 2010 household survey of 6879 households in 9 provinces of Afghanistan were linked to routine facility data. Hierarchical logistic regression models were used to assess determinants of skilled birth attendance. Results: Women who reported having at least one antenatal visit with a skilled provider were 5.6 times more likely to give birth with a skilled attendant than those who did not. The odds of skilled birth attendance were 84% higher for literate women than those without literacy skills and 79% higher among women in the upper 2 wealth quintiles than women in the poorest quintile. This study did not show any direct linkages between facility characteristics and skilled birth attendance but provided insights into why studies assuming that women seek care at the nearest primary care facility may lead to misinterpretation of care‐seeking patterns. Findings reveal a 36 percentage point gap between women who receive skilled antenatal care and those who received skilled birth care. Nearly 60% of women with a skilled attendant at their most recent birth bypassed the nearest primary care facility to give birth at a more distant primary care facility, hospital, or private clinic. Distance and transport barriers were reported as the most common reasons for home birth. Discussion: Assumptions that women who give birth with a skilled attendant do so at the closest health facility may mask the importance of supply‐side determinants of skilled birth attendance. More research based on actual utilization patterns, not assumed catchment areas, is needed to truly understand the factors influencing care‐seeking decisions in both emergency and nonemergency situations and to adapt strategies to reduce preventable mortality and morbidity in Afghanistan.